Rspo1/Rspo3-LGR4 signaling inhibits hepatic cholesterol synthesis through AMPKα-SREBP2 pathway - Liu, Shiying (FASEB J, 2020)
R-spondins (Rspos) are endogenous ligands of leucine-rich repeat-containing G-protein coupled receptor 4 (LGR4). Rspos-LGR4 signaling plays important roles in embryogenesis, gastrointestinal homeostasis and food intake. Here, we investigated impacts of Rspos-LGR4 on hepatic cholesterol synthesis. Rspo1/3 and Lgr4 knockdown mice were used to investigate the impacts of Rspo1/3-LGR4 on hepatic cholesterol synthesis. AMPKα agonist, antagonist and shRNA were used to explore the downstream targets of Rspos-LGR4 signaling. In our study, we reported that LGR4, Rspo1 and Rspo3 were highly expressed in hepatocytes and their expressions were sensitive to energy states. Rspo1 and Rspo3 reversed OA-induced cholesterol synthesis, accompanying with increased phosphorylation of AMPKα Thr172, reduced SREBP2 nuclear translocation and Srebf2 mRNA expression. Conversely, hepatic LGR4 knockdown increased hepatic cholesterol synthesis and decreased phosphorylation of AMPKα both in vitro and in vivo. Activation or inhibition of AMPKα significantly abolished the effects of LGR4 deficiency or Rspos, respectively, on cholesterol synthesis. Knockdown of AMPKα1 or/and AMPKα2 repressed Rspos induced inhibition on cholesterol synthesis. Our study indicates that Rspo1/Rspo3-LGR4 signaling in hepatocytes suppresses cholesterol synthesis via AMPKα-SREBP2 pathway.